Β‐Adrenergic signaling in skin cancer. Issue 4 (6th January 2022) - Batalla‐Covello, Jennifer; Ali, Shahrukh; Xie, Tongxin; Amit, Moran
Abstract: Activation of the sympathetic nervous system releases catecholamines that can interact with β‐adrenergic receptors on tumor cells. Preclinical models have shown that the signaling processes initiated by activation of β‐adrenergic receptors increase tumorigenesis, stimulate cell proliferation, and inhibit apoptosis. Indeed, preclinical studies have also shown that β‐adrenergic blockade can decrease tumor burden. Researchers have been studying the effects of β‐adrenergic receptor blockers on tumor cells and how they may slow the progression of melanoma, basal cell carcinoma, and squamous cell carcinoma. Moreover, clinical data have shown improved prognosis in patients with skin cancer who take β‐blockers. This review discusses the mechanisms of β‐adrenergic signaling in cancer and immune cells, details preclinical models of sympathetic blockade, and considers clinical evidence of the effects of β‐adrenergic blockade in skin cancers.